Peregrinação - Silva, Cláudio da, 1974-; Carneiro, Cassiano, 1973-; Inês, Pedro; Pinto, Fernão Mendes, -1583 (Ar de Filmes, 2017)
A remarkable imagining of the historic voyages of 16th-century explorer and writer Fernão Mendes Pinto, one of the first Europeans to sail to and travel the Orient-- India, Japan, and places in between. --